Single cell RNA-sequencing and RNA-tomography of the avian embryo extending body axis - Mok, G. F.; Turner, S.; Smith, E. L.; Mincarelli, L.; Lister, A.; Lipscombe, J.; Uzun, V.; Haerty, W.; Macaulay, I. C.; Münsterberg, A. E. (Frontiers in Cell and Developmental Biology, 2024)
Introduction: Vertebrate body axis formation initiates during gastrulation and continues within the tail bud at the posterior end of the embryo. Major structures in the trunk are paired somites, which generate the musculoskeletal system, the spinal cord—forming part of the central nervous system, and the notochord, with important patterning functions. The specification of these different cell lineages by key signalling pathways and transcription factors is essential, however, a global map of cell types and expressed genes in the avian trunk is missing. Methods: Here we use high-throughput sequencing approaches to generate a molecular map of the emerging trunk and tailbud in the chick embryo. Results and Discussion: Single cell RNA-sequencing (scRNA-seq) identifies discrete cell lineages including somites, neural tube, neural crest, lateral plate mesoderm, ectoderm, endothelial and blood progenitors. In addition, RNA-seq of sequential tissue sections (RNA-tomography) provides a spatially resolved, genome-wide expression dataset for the avian tailbud and emerging body, comparable to other model systems. Combining the single cell and RNA-tomography datasets, we identify spatially restricted genes, focusing on somites and early myoblasts. Thus, this high-resolution transcriptome map incorporating cell types in the embryonic trunk can expose molecular pathways involved in body axis development.